Destructive and non-destructive properties of cobalt oxide substituted 1393 bioactive glass - Yadav S.K.; Vyas V.K.; Anand P.; Majhi M.R.; Pyare R. (My University, 2025)
This study is based on two types of tests; the first one is destructive and second is non- destructive. The mechanical properties of the sample were measured without destruction of the sample since the biomaterials were costly to prepare. In this study, cobalt oxide containing 1393 bioactive glass of general molar composition [(53-X) SiO2- 6Na2O- 20CaO-4 P2O5-12K2O-5MgO+XCoO)] (where X= 0 to 1.65 mol %) was melted in an alumina crucible (99.7%) in an electric furnace at a temperature of 1400°C with air as furnace atmosphere. The structure of bioactive glass was evaluated using FTIR and XRD techniques. The destructive tests like micro hardness, compressive, flexural strengths and the non-destructive tests of elastic moduli were carried out. It was observed that substitution of cobalt oxide for silica in 1393 bioactive glass improved its density, compressive and flexural, micro hardness and elastic properties. © RASĀYAN. All rights reserved.